Impact of End-Effector Device on Gait Restoration in Children Suffering from Neurological Disorders - Malovec, Martin (Archives of Clinical and Biomedical Research, 2024)
Background: Gait disorders in children with neurological conditions significantly impact their independence and quality of life. Traditional rehabilitation methods have several limitations, highlighting the need for innovative solutions. Robotic-assisted gait training appears to be a promising approach for improving gait difficulties in this population. Objective: This study aims to evaluate the effectiveness of a novel endeffector type of robot-assisted gait training system in addressing gait difficulties in pediatric patients with neurological disorders. Material and methods: Twenty-five patients with gait-related neurological disorders underwent 10 therapy sessions (each lasting 30 minutes) using an end-effector RAGT device in conjunction with conventional therapy. Gait parameters, including the number of steps, distance walked, and speed, were compared based on data collected during the first and last therapy sessions. Results: Statistically significant improvements were observed in all assessed parameters for both patient groups, with an average increase of approximately 48% in the number of steps, 63% in distance walked, and 39% in walking speed. The differences between the groups were minimal, with slightly better outcomes noted in the CP group. Conclusion: Following therapy with the end-effector-based RAGT system, all assessed parameters showed notable improvements in both patient groups, indicating its positive impact on gait ability across various pediatric neurological conditions.